Myocardial Iron Overload in an Experimental Model of Sudden Unexpected Death in Epilepsy - Akyuz, Enes; Doganyigit, Zuleyha; Eroglu, Ece; Moscovicz, Franco; Merelli, Amalia; Lazarowski, Alberto; Auzmendi, Jerónimo (Frontiers in Neurology, 2021)
Iron deposition in the heart is an important factor leading to heart failure. "Iron-Overloaded Cardiomyopathy" (IOC) has been related with a new mechanism of death defined as "ferroptosis" and associated with heart failure and sudden cardiac death. Ferroptosis is an iron-dependent, but non-apoptotic cell death that induces tissue damage by iron overload. Under this condition, high levels of intracellular ferritin are dehydrated and converted into aggregates of hemosiderin. This complex mix of iron deposit can be quantified in vivo by Cardiovascular Magnetic Resonance Imaging T2∗. In sudden unexpected death in epilepsy (SUDEP), heart failure may develop as a result of a high rate of convulsive hypoxic stress with excessive sympathetic overstimulation triggering a neuro-cardiogenic injury, also defined as the "Epileptic Heart". Here we demonstrated at the first time that experimental repetitive generalized tonic-clonic seizures associated with high rates of SUDEP were concomitantly related to hemosiderin accumulation in the heart. This suggests that uncontrolled recurrent seizures, as observed in refractory epilepsy, could be a high stress burden that induce the IOC, and acting as underlying silent mechanism that contribute to the developing heart failure and SUDEP.